Well-being among survivors of out-of-hospital cardiac arrest: a cross-sectional retrospective study in Sweden. Issue 6 (6th June 2018) - Viktorisson, Adam; Sunnerhagen, Katharina S; Pöder, Ulrika; Herlitz, Johan; Axelsson, Åsa B
Abstract : Objectives: The psychological outcome of out-of-hospital cardiac arrest (OHCA) has been studied more extensively in recent years. Still, not much is known about the well-being among OHCA survivors. In this retrospective cross-sectional study, we aim to investigate post-OHCA well-being among patients with a good neurological outcome, 3 months after the cardiac event. To assess well-being, we analyse the frequency of anxiety, depression, post-traumatic stress disorder (PTSD) and health within this group. Further, we aim to evaluate the importance of five prognostic factors for post-OHCA well-being. Methods: Data collection took place between 2008 and 2012, and every OHCA survivor within one region of Sweden, with a cerebral performance category (CPC) score of ≤2 at discharge, was asked to participate. Survivors were identified through the Swedish Cardiopulmonary Resuscitation Registry, and postal questionnaires were sent out 3 months after the OHCA. The survey included Hospital Anxiety and Depression scale (HADS), PTSD Checklist Civilian version (PCL-C) and European Quality of Life 5 Dimensions 3 level (EQ-5D-3L). Results: Of 298 survivors, 150 were eligible for this study and 94 responded. The mean time from OHCA to follow-up was 88 days. There was no significant difference between respondents and non-respondents in terms of sex, age, cardiac arrest circumstances or in-hospital interventions. 48 participants reported reduced well-being, and young age was the only factor significantly correlated to this outcome (p=0.02). Women reported significantly higher scores in HADS (p=0.001) and PCL-C (p<0.001). Women also reported significantly lower EQ-5D index values (p=0.002) and EQ-visual analogue scale scores (p=0.002) compared with men. Conclusion: Reduced well-being is experienced by half of OHCA survivors with a CPC score ≤2, and young age is negatively correlated to this outcome. The frequency of anxiety and PTSD is higher among women, who also report worse health.